2000
DOI: 10.1088/0031-9155/45/7/306
|View full text |Cite
|
Sign up to set email alerts
|

150-250 MeV electron beams in radiation therapy

Abstract: High-energy electron beams in the range 150-250 MeV are studied to evaluate the feasibility for radiotherapy. Monte Carlo simulation results from the PENELOPE code are presented and used to determine lateral spread and penetration of these beams. It is shown that the penumbra is comparable to photon beams at depths less than 10 cm and the practical range (Rp) of these beams is greater than 40 cm. The depth dose distribution of electron beams compares favourably with photon beams. Effects caused by nuclear reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
150
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(158 citation statements)
references
References 24 publications
8
150
0
Order By: Relevance
“…Monte Carlo simulations with the FLUKA generalpurpose code confirm the EBT2 Gafchromic film method of dosimetry and demonstrate the usefulness of the code for interpreting experimental studies using very high energy electron beams in the range of 130-170 MeV. It has also been calculated that the neutron yield is lower than predicted in early studies of VHEE (DesRosiers et al 2000). EBT2 dosimetry will underpin any further work aiming to demonstrate versatility of potential application of VHEEs to radiotherapy.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Monte Carlo simulations with the FLUKA generalpurpose code confirm the EBT2 Gafchromic film method of dosimetry and demonstrate the usefulness of the code for interpreting experimental studies using very high energy electron beams in the range of 130-170 MeV. It has also been calculated that the neutron yield is lower than predicted in early studies of VHEE (DesRosiers et al 2000). EBT2 dosimetry will underpin any further work aiming to demonstrate versatility of potential application of VHEEs to radiotherapy.…”
Section: Discussionmentioning
confidence: 71%
“…Previous theoretical studies using the PENELOPE code (DesRosiers et al 2000, Moskvin et al 2010 have shown the potential of 150-250 MeV VHEE beams for radiotherapy. The effective range of such beams can exceed 40 cm and, moreover, lateral scattering of high-energy electrons in tissue is sufficiently small for use in IMRT treatment of deep seated tumours Sandison 2002, Fuchs et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…4 -7 VHEEB are superior to photon beams due to their specific physical properties of dose deposition, as attested to by the following factors: ͑1͒ the ratio of integral dose to the target, compared with the integral dose to healthy tissue/sensitive organs, is higher for VHEEB than for photon beams, 4 -7 and ͑2͒ the absence of electronic disequilibrium at interfaces for VHEEB therapy avoids under-and over-dosage at boundaries of organs, and leads to a more uniform dose distribution throughout the target. 4,5 VHEEB can be scanned at a speed and intensity that allows simultaneous tracking and IMRT treatment of moving or deformable targets, a feature absolutely necessary for 4D-IMRT. This feature is facilitated by high dose rates of VHEEB ͑of the order of Gy/s͒, making possible nearly instantaneous ͑1-2 sec͒ delivery of the full dose per fraction per field.…”
Section: Opening Statementmentioning
confidence: 99%
“…It also helps assure independence of dose contributions to each point from individual pencil beams. 4,5 In contrast to photon MLC IMRT, VHEEB pencil beam independence ensures that dose calculations for VHEEB IMRT can be accurately determined through linear ͑additive͒ operations. Furthermore, optimal intensity maps for VHEEB treatments are directly deliverable without being compromised by contamination and scattering characteristics encountered with photon MLC treatments.…”
Section: Opening Statementmentioning
confidence: 99%
“…Owing to continuous improvements in laser systems and gas target technology (Semushin & Malka, 2001;Spence & Hooker, 2001), stable generation of well-collimated, quasi-monoenergetic, hundred-megaelectronvolt (MeV)-scale electron beams from millimeter to centimeter-length plasmas has become experimentally routine (Brunetti et al, 2010;Faure et al, 2006;Hafz et al, 2008;Leemans et al, 2006;Maksimchuk et al, 2007;Malka et al, 2009;Mangles et al, 2007;Osterhoff et al, 2008). These beams have been used for a broad range of technical and medical physics applications -γ-ray radiography for material science Ramanathan et al, 2010), testing of radiation resistivity of electronic components used in harsh radiation environments (Hidding et al, 2011), efficient on-site production of radioisotopes (Leemans et al, 2001;Reed et al, 2007), and radiotherapy with tunable, high-energy electrons (DesRosiers et al, 2000;Glinec et al, 2006;Kainz et al, 2004). Their unique properties -femtosecond (fs)-scale duration and multi-kiloampere current (Buck et al, 2011;Lundh et al, 2011) -are clearly favorable for ultrafast science applications, such as high-energy radiation femtochemistry (Brozek-Pluska et al, 2005), spatio-temporal radiation biology and radiotherapy , and compact x-ray sources (Fuchs et al, 2009;Grüner et al, 2007;Hartemann et al, 2007;Kneip et al, 2010;Pukhov et al, 2010;Rousse et al, 2007;Schlenvoigt et al, 2008).…”
Section: Introductionmentioning
confidence: 99%